A prática de um Conselho de Política Pública: a efetivação da participação social a nível local - Cunha, Elãine Novak Lacomski (2021)
This research sought to reflect on the practice of a Municipal Council in the public policy of Social Assistance in the city of Prudentópolis (PR). This is a qualitative research which sought to understand, based on discourse analysis and on the Critical Epistemology of Concrete, how the members of the collegiate body and a representative of the Municipal Social Assistance Department perceive themselves as subjects in the Council's participatory process. , considering the social participation established after the democratic rule of law, considering the collective construction of public policies and the actions of social control exercised by the population in the construction, monitoring and evaluation of these, in this specific case, the public policy on social assistance. The collection of primary data took place through semi-structured interviews with the aforementioned research subjects. As for the secondary data, these refer to the minutes and documents prepared by the collegiate body in the years 2019 and 2020, as well as the legislation that regulates the Council in the municipality. From this study, it can be seen that, despite being established for years, the collegiate body is considered here to rotate between members from time to time, it does not exercise its real function continuously and clearly at certain times and issues. , which is the process of collective construction, monitoring and evaluation of public social assistance policy, the Council appears in many acts only as a place that endorses public administration actions, a deliberative and propositional Council is not seen, with actions that encourage and enable social participation. In this juncture, there is a collegiate body restricted to punctual and proforma actions in its existence. There is a lack of acts that implement in fact and in law this collegiate body in accordance with the principles for which it was created, that is, social participation and social control, aiming at a public, collective and guarantor of rights.The results obtained show that the CMAS presents a representation that does not correspond to the real foundation of social participation, considering that the participation of its members is not effective due to a performance restricted only to the list of members, in certain circumstances not even the directors (as) are clear about their role and/or are able to participate in the meetings, verifying a more directive action by the government sector. Such organicity hinders the effective realization of the nature of the CMAS, in which themes of interest to the community are not guided, thus favoring its instrumental character. The documents produced present data and information, mostly in a checklist style, which contributes to a restricted and veiled role of the Board, since there were no channels of external dissemination of the CMAS, thus verifying that in many moments a pro-forma role of the CMAS takes place at the expense of the real assumptions of social participation and a space for collective and proactive construction of the PMAS.